2005
DOI: 10.1079/bjn20041390
|View full text |Cite
|
Sign up to set email alerts
|

Maternal dietary 22: 6n-3 is more effective than 18: 3n-3 in increasing the 22: 6n-3 content in phospholipids of glial cells from neonatal rat brain

Abstract: One of the debates in infant nutrition concerns whether dietary 18: 3n-3 (linolenic acid) can provide for the accretion of 22: 6 n-3 (docosahexaenoic acid, DHA) in neonatal tissues. The objective of the present study was to determine whether low or high 18: 3 n-3 v. preformed 22: 6 n-3 in the maternal diet enabled a similar 22: 6 n-3 content in the phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI) and phosphatidylserine (PS) of glial cells from whole brain (cerebrum and cerebel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 133 publications
(122 reference statements)
5
43
0
3
Order By: Relevance
“…Increased availability of DHA increases PtdCho synthesis in fetal lung explants by a direct stimulatory effect of DHA on the rate-limiting enzyme in the pathway, CTP: choline cytidylyltransferase (42), and if the same effect occurs in fetal brain, it may contribute to the changes in PtdCho-DHA that we report. Other studies reported that increasing maternal dietary DHA increased DHA content of PtdEtn and PtdSer of whole brain glial cells in rat pups (43). We found this to be true, along with similar effects on PtdIns-DHA, in fetal brains from the Pemt Ϫ/Ϫ pups whose dams were fed a diet supplemented with DHA (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 66%
“…Increased availability of DHA increases PtdCho synthesis in fetal lung explants by a direct stimulatory effect of DHA on the rate-limiting enzyme in the pathway, CTP: choline cytidylyltransferase (42), and if the same effect occurs in fetal brain, it may contribute to the changes in PtdCho-DHA that we report. Other studies reported that increasing maternal dietary DHA increased DHA content of PtdEtn and PtdSer of whole brain glial cells in rat pups (43). We found this to be true, along with similar effects on PtdIns-DHA, in fetal brains from the Pemt Ϫ/Ϫ pups whose dams were fed a diet supplemented with DHA (Tables 1 and 2).…”
Section: Discussionsupporting
confidence: 66%
“…DHA may be synthesised from its precursor, a-linolenic acid (LNA) via eicosapentaenoic acid (EPA), and is thought to be selectively transported across the placenta (Haggarty et al, 1997;Dutta-Roy, 2000). It remains unclear whether endogenous synthesis of DHA is always adequate to meet the needs of the developing neonatal brain (Bowen and Clandinin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Ixtaina et al (2011) relatam que a incorporação de sementes de chia na dieta seria benéfico, devido ao elevado teor de AGP presentes na sua composição (9,2%). De acordo com Bowen et al (2005) o consumo de óleos com elevados teores de AGPs pode fornecer benefícios a saúde, além de tornar o óleo mais estável). O óleo extraído das sementes de chia apresentou uma relação AGPI: AGS >11, considerado adequado para alimentos (Matsushita et al, 2010;Ramos-Filho et al, 2008;França et al, 2011).…”
Section: Quantificação De áCidos Graxos Totaisunclassified